Calculation of the specific heat close to the multicritical and second order phase regions in ND4Cl - Yurtseven, Hamit; Yanık, Askin (Springer Science and Business Media LLC, 2007)
We calculated the specific heat C V of ND4Cl under the prediction of an Ising model presented here. Our calculated C V agrees with the experimental C P data for the multicritical (P = 0.1 MPa) and second order (P = 150 MPa) phase regions in this crystalline system. This agreement is particularly good above T C $$ ( \cong $$ 250 K) for the multicritical regime and below T C $$ (\cong $$ 261 K) for the second order phase transition in ND4Cl. This shows that the observed behaviour of ND4Cl can be well described by an Ising model close to the phase transitions considered in this crystalline system.